MTCH2-mediated mitochondrial fusion drives exit from naïve pluripotency in embryonic stem cells - Amir Bahat (Nature Portfolio, 2018)
Reprogramming of mitochondria metabolism occurs during naïve to primed pluripotency differentiation in mouse embryonic stem cells (ESCs). Here the authors show that mitochondrial MTCH2 regulates mitochondrial fusion and that this fusion is required for naïve to primed pluripotency conversion